Packing dimensions of basins generated by distributions on a finite alphabet - Bakhtin, Victor I.; Sadok, Bruno (Journal of the Belarusian State University. Mathematics and Informatics, 2021)
We consider a space of infinite signals composed of letters from a finite alphabet. Each signal generates a sequence of empirical measures on the alphabet and the limit set corresponding to this sequence. The space of signals is partitioned into narrow basins consisting of signals with identical limit sets for the sequence of empirical measures and for each narrow basin its packing dimension is computed. Furthermore, we compute packing dimensions for two other types of basins defined in terms of limit behaviour of the empirical measures.